The The Impact of Green Credit Policies on the Financial Performance of Indonesian Banking: English - Jessica Yunanda Bahtiar; Taufik Faturohman (Journal Integration of Management Studies, 2026)
This study analyzes the impact of Green Credit Policies (GCP) on the financial performance of Indonesian banking institutions. Utilizing a framework grounded in stakeholder and legitimacy theories, this research examines the extent to which green credit initiatives influence key financial metrics, specifically Return on Equity (ROE) and Earnings Per Share (EPS). The dataset comprises a panel of 33 Indonesian banks observed from 2020 to 2024. Panel data regression models were applied to test the hypothesized relationships. The findings indicate a positive correlation between GCP and financial performance, suggesting that transparency and sustainability practices foster financial resilience and long-term sustainability. To address potential endogeneity bias and reverse causality, robustness checks were conducted to validate the empirical results. This study contributes to the green finance literature by providing empirical evidence regarding the financial benefits of GCP implementation. The implications advocate for regulatory frameworks that promote transparency, highlighting that integrating sustainability into corporate strategies enhances competitive advantage and profitability.